1997
DOI: 10.1038/sj.onc.1201371
|View full text |Cite
|
Sign up to set email alerts
|

v-Abl protein tyrosine kinase (PTK) mediated suppression of apoptosis is associated with the up-regulation of Bcl-XL

Abstract: We demonstrated previously that the activation of v-Abl protein tyrosine kinase (PTK) in IC.DP murine pre-mast cells resulted in suppression of apoptosis after withdrawal of interleukin 3 (IL-3), that protein kinase C (PKC) translocated to the nucleus 6 h after v-Abl PTK activation and that inhibition of PKC restored apoptosis after IL-3 deprivation in the presence of v-Abl PTK activity. Here we demonstrate that v-Abl PTK activation is followed by an approximately twofold increase in mRNA level of Bcl-X L by 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…This is in agreement with our results showing the dramatic reduction of Bcl-x expression in Ba/F3D749 cells in absence of IL-3. Similarly, it has been shown that suppression of apoptosis mediated by Bcr-abl or v-abl was independent of Bcl-2 expression but was correlated with up-regulation of Bcl-x L (Amarente- Mendes et al, 1998;Chen et al, 1997). Altogether these results support our data that inhibition of Bcl-x by the dominant negative form of STAT5 coincide with an increase of apoptosis in Ba/F3 cells in absence of IL-3.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with our results showing the dramatic reduction of Bcl-x expression in Ba/F3D749 cells in absence of IL-3. Similarly, it has been shown that suppression of apoptosis mediated by Bcr-abl or v-abl was independent of Bcl-2 expression but was correlated with up-regulation of Bcl-x L (Amarente- Mendes et al, 1998;Chen et al, 1997). Altogether these results support our data that inhibition of Bcl-x by the dominant negative form of STAT5 coincide with an increase of apoptosis in Ba/F3 cells in absence of IL-3.…”
Section: Discussionsupporting
confidence: 91%
“…Activation of tyrosine kinases and phosphoinositide 3Ј-kinase (PI3Ј-K) has been implicated in the induction of mast cell growth (19 -21). Other studies have shown a decrease in the protooncogene bcl-2 after removal of IL-3; moreover, overexpression of bcl-2 prolongs the survival of mast cells after IL-3 removal (22)(23)(24)(25)(26)(27)(28)(29). In contrast, SCF does not appear to influence bcl-2 expression (14).…”
mentioning
confidence: 86%
“…As 2 O 3 -treated cells were fractionated by differential centrifugation as described previously [43][44][45]. Briefly, cells were harvested through trypsin digestion, and then centrifuged and resuspended in three volumes of hypotonic buffer (210 mM sucrose, 70 mM mannitol, 10 mM HEPES (pH 7.4), 1 mM EDTA) containing 1 mM PMSF, 50 mg/ml trypsin inhibitor, 10 mg/ml leupeptin, 5 mg/ml aprotinin and 10 mg/ml pepstatin.…”
Section: Cell Fractionationmentioning
confidence: 99%